Cointegration analysis between SES all-s indices and macroeconomic variables. - Mohamad Atkin Hamzah. (2008)
This article examines the long-term equilibrium relationships between the overall Singapore stock index, finance index, property index, hotel index and selected macroeconomic variables. Upon testing appropriate vector error-correction models, we detected the Singapore’s stock market levels and property index do form cointegrating relationship with changes in the short and long-term interest rates, industrial production, price levels, exchange rate and money supply.